2021
DOI: 10.1186/s13229-020-00410-w
|View full text |Cite
|
Sign up to set email alerts
|

Touch and olfaction/taste differentiate children carrying a 16p11.2 deletion from children with ASD

Abstract: Background Sensory processing atypicalities are frequent in Autism Spectrum Disorder (ASD) and neurodevelopmental disorders (NDD). Different domains of sensory processing appear to be differentially altered in these disorders. In this study, we explored the sensory profile of two clinical cohorts, in comparison with a sample of typically developing children. Methods Behavioral responses to sensory stimuli were assessed using the Sensory Processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 84 publications
2
8
0
Order By: Relevance
“…The relationship observed between autistic symptomatology and sensory differences indicates that children with a 16p11.2 deletion and duplication who experience autistic symptomatology are also likely to experience sensory differences. The observed relationship in 16p11.2 deletion is also consistent with findings reported by Osório, Rodríguez‐Herreros, Romascano, et al ( 2021 ). They reported that ADOS‐2 Total Scores and Social Affect (SA) scores, but not Restricted and Repetitive Behavior (RRB) scores, were associated with sensory differences in 16p11.2 deletion children.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The relationship observed between autistic symptomatology and sensory differences indicates that children with a 16p11.2 deletion and duplication who experience autistic symptomatology are also likely to experience sensory differences. The observed relationship in 16p11.2 deletion is also consistent with findings reported by Osório, Rodríguez‐Herreros, Romascano, et al ( 2021 ). They reported that ADOS‐2 Total Scores and Social Affect (SA) scores, but not Restricted and Repetitive Behavior (RRB) scores, were associated with sensory differences in 16p11.2 deletion children.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, our findings in relation to 16p.11.2 deletion are broadly in alignment with those reported on a smaller 16p11.2 deletion cohort by Osório, Rodríguez‐Herreros, Romascano, et al ( 2021 ). However, a key difference from the findings reported by Osório, Rodríguez‐Herreros, Romascano, et al ( 2021 ) was that the current study found children with a 16p11.2 deletion exhibited differences in the processing of touch or oral (response to smells or touch/taste in the mouth) sensory information. Clear differences in touch and oral systems were present in both autistic and non‐autistic 16p11.2 children (although were somewhat less common in non‐autistic children).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…E. Lane et al, 2014;Little et al, 2017a). For instance, modalities such as audition, taste-smell and touch seem to discriminate individuals with ASD from other clinical groups (Little et al, 2017b;McCormick et al, 2016;Os orio et al, 2021;Schaaf & Lane, 2015;Tomchek & Dunn, 2007;Wiggins et al, 2009).In this context, using modality-based approaches to the study of sensory systems could provide more information on how sensory modalities contribute to the different subtypes of sensory difficulties, and whether these are specific to one or more NDD (DeBoth & Reynolds, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Over and under‐responses to sensory stimuli can have high levels of co‐occurrence (Ben‐Sasson et al, 2019 ; Dellapiazza et al, 2019 ), and they can also occur in different patterns across different modalities (Ausderau et al, 2014 ; Ausderau et al, 2016 ; DeBoth & Reynolds, 2017 ; A. E. Lane et al, 2011 ; A. E. Lane et al, 2014 ; Little et al, 2017a ). For instance, modalities such as audition, taste–smell and touch seem to discriminate individuals with ASD from other clinical groups (Little et al, 2017b ; McCormick et al, 2016 ; Osório et al, 2021 ; Schaaf & Lane, 2015 ; Tomchek & Dunn, 2007 ; Wiggins et al, 2009 ).In this context, using modality‐based approaches to the study of sensory systems could provide more information on how sensory modalities contribute to the different subtypes of sensory difficulties, and whether these are specific to one or more NDD (DeBoth & Reynolds, 2017 ).…”
Section: Introductionmentioning
confidence: 99%